INVALIDADES EM CONTRATOS DE CONSUMO (De Legibus - Law Journal, 2021)
This essay is about the special rules on invalidities of consumer contracts. Consumer contracts are contracts of private law regulated by a special regime. In the absence of this regime, the common private rules apply. I try to discover differences and connections between those special rules and general rules.
Keywords: Consumer Contracts; Invalidity